Beyond the Big Five: Investigating Myostatin Structure, Polymorphism and Expression in Camelus dromedarius - Favia, Maria; Fitak, Robert; Guerra, Lorenzo; Pierri, Ciro Leonardo; Faye, Bernard; Oulmouden, Ahmad; Burger, Pamela Anna; Ciani, Elena (Frontiers in Genetics, 2019)
Myostatin, a negative regulator of skeletal muscle mass in animals, has been shown to play a role in determining muscular hypertrophy in several livestock species, and a high degree of polymorphism has been previously reported for this gene in humans and cattle. In this study, we provide a characterization of the myostatin gene in the dromedary (Camelus dromedarius) at the genomic, transcript and protein level. The gene was found to share high structural and sequence similarity with other mammals, notably Old World camelids. 3D modeling highlighted several non-conservative SNP variants compared to the bovine, as well as putative functional variants involved in the stability of the myostatin dimer. NGS data for nine dromedaries from various countries revealed 66 novel SNPs, all of them falling either upstream or downstream the coding region. The analysis also confirmed the presence of three previously described SNPs in intron 1, predicted here to alter both splicing and transcription factor binding sites (TFBS), thus possibly impacting myostatin processing and/or regulation. Several putative TFBS were identified in the myostatin upstream region, some of them belonging to the myogenic regulatory factor family. Patterns of SNP distribution across countries, as suggested by Bayesian clustering of the nine dromedaries using the 69 SNPs, pointed to weak geographic differentiation, in line with known recurrent gene flow at ancient trading centers along caravan routes. Myostatin expression was investigated in a set of 8 skeletal muscles, both at transcript and protein level, via Digital Droplet PCR and Western Blotting, respectively. No significant differences were observed at the transcript level, while, at the protein level, the only significant differences concerned the promyostatin dimer (75 kDa), in four pair-wise comparisons, all involving the tensor fasciae latae muscle. Beside the mentioned band at 75 kDa, additional bands were observed at around 40 kDa and 25 kDa, corresponding to the promyostatin monomer and the active C-terminal myostatin dimer, respectively. Their weaker intensity suggests that the unprocessed myostatin dimers could act as important reservoirs of slowly available myostatin forms. Under this assumption, the sequential cleavage steps may contribute additional layers of control within an already complex regulatory framework.